Qualidade vocal e processamento auditivo em indivíduos com e sem prática musical - Paoliello, Karla Barbosa Guarda [UNIFESP] (2017)
INTRODUCTION: The relationship between voice and auditory processing is complex and has aroused greater scientific interest in the last decades. However, little is known about the relationship between vocal quality and auditory processing in individuals with and without musical practice. OBJECTIVES: To verify the vocal quality and the physiological mechanisms of selective attention and temporal ordering in individuals with and without musical practice. METHODS: 136 individuals were divided into three groups: G1 = singers, G2 = instrumentalists and G3 = without musical practice, non-singers and non-instrumentalists; The G1 group was subdivided into G1.1 = instrumentalist singers and G1.2 = singers only. The subjects underwent vocal evaluation through auditory perceptual analysis (APA) of the recording of their spoken voices, categorizing them and self - assessment of a possible voice problem through the Vocal Symptom Scale - VoiSS. The participants had their central auditory processing evaluated by the following tests: Pattern Frequency Test (FPT), Random Gap Detection Test (RGDT), Staggered Spondaic World (SSW), Speech in Noise and Synthetic Sentence Identification (SSI). The correlation between voice and auditory abilities was studied. RESULTS: The majority of individuals in all the groups studied did not present vocal deviation, which when it occurred was of a discrete degree; (G1.1 = 46.15% and G2 = 18.18%) and 1 (G1.1 = 46.15% and G2 = 75%). There was no statistically significant association between the various APA levels and the sexes evaluated. G1 reported more vocal symptoms than the other groups with averages above 16 points in the ESV, with G1.2 presenting a mean of 23.86 and G1.1 of 21.70; Women had higher scores on total ESV (20.55) and Limitation (11.25). The G1.1 subgroup showed higher auditory temporal ordering ability in the TPF, both in Humming (OD = 100% and OE = 99.75%), and in Nomination (OD = 96.89% and EO = 97.77 %), with G3 showing the lowest averages; males were better in both TPF (Humming OD = 97.74% and EO = 97.66%, ND = 94.15% and EO = 94.60%), as in RGDT (4.48). Only negligible strength correlations were found between the different central auditory processing tests, the general degree of vocal deviation in the auditory perceptual analysis of vocal quality, and the different scores of the Signals and Vocal Symptoms Scale protocol. CONCLUSION: The vocal quality of musicians and non-musicians correlated with their auditory processing, although with negligible strength. It was found that the singers reported more vocal symptoms in relation to the other groups, due to the probable awareness of their instrument, as well as the women when compared to the men. As for auditory processing, there was great variation in all groups. However, musicians, mainly instrumental singers, demonstrated a better auditory ability of temporal ordering, suggesting that the study and musical experience can be responsible for this performance. For this same aspect, regarding the influence of gender on the auditory abilities, it was verified that the men have better results in the tests of ordering and temporal resolution.